Language Choice of Residents of Kampung Warna–Warni Malang to the Tourists - Ismatul Khasanah; Roosi Rusmawati; Khilmi Mauliddian; Arief Nur Rohman Hakim (IAIN MADURA, 2020)
Residents' language choice of Kampung Warna - Warni Malang towards tourists is an interesting study as the linguistics phenomenon from a sociolinguistic's perspective affects both social and cultural life there. The study aims to describe the resident's language choice through daily interaction between the residents and the tourists. The writer used a qualitative method to provide a general description of the phenomenon as clearly as possible without any interference to observed study subjects. This research was a sociolinguistic study based on the language phenomena that occurred in the tourism spot which is originally considered as slums in recent years before went through many beautifications from many parties. The result found that the residents tend to use code-switching from Javanese, both Ngoko and Krama form, and Indonesian to converse with domestic tourists. Meanwhile, the locals tend to shy away from conversing with international tourists except for a simple greeting, a simple gesture of navigating direction, and a simple yes or no question due to the language barrier